Analisis Peluang dan Tantangan Penggunaan Financial Technology (Fintech) pada UMKM di Kabupaten Banyumas - Silvia Van Marsally; Hanif Febri Nugroho; Salma Eka Saputri; Ribka Tavania; Rangga Ferdyansyah Saputro (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This research aims to analyze the opportunities and challenges of implementing financial technology (Fintech) in Micro, Small, and Medium Enterprises (MSMEs) in Banyumas Regency. Banyumas was chosen as the research location because it has good potential for the development of MSMEs. This study uses a qualitative descriptive approach, analyzing data obtained from information and interviews with MSME actors. Based on the research results, it is concluded that MSME actors have a good understanding of fintech as a financial technology innovation that can help operational efficiency for MSMEs. MSME actors recognize the importance of using fintech today; they experience ease and efficiency in payment transactions, potential for sustainable growth, increased competitiveness in the digital economy era, and the potential to boost sales. However, in its implementation, MSMEs face several obstacles and challenges in using fintech, including security and privacy factors, the lack of interest and understanding of fintech usage by consumers, the risk of cybercrime, and limited internet access. Therefore, support from various parties such as the government, industry, and the wider community is needed to optimize the benefits of fintech.